STRATEGIC COLLABORATION BETWEEN HRM AND HALAL PRODUCT MANAGEMENT IN BUILDING COMPETITIVE ADVANTAGE: EVIDENCE FROM HALAL BASED SMES IN NORTH SUMATRA - Hasibuan, Desi Seprina Yanti; Zulkarnaini, Zulkarnaini; Ichsan, Reza Nurul; Chaniago, Sabaruddin (Journal of Sustainable Business, Economics and Accounting, 2026)
This study investigates the strategic collaboration between Human Resource Management (HRM) and Halal Product Management (HPM) in creating sustainable competitive advantage among halal-based Small and Medium Enterprises (SMEs) in North Sumatra, Indonesia. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), this research analyzes data from 285 halal-certified SMEs operating across food manufacturing, cosmetics, pharmaceuticals, and fashion sectors. The findings reveal that strategic HRM practices—encompassing halal-aware recruitment, sharia-compliant training, and Islamic work ethics—significantly enhance halal product management capabilities (β = 0.418, p < 0.001). Furthermore, the synergistic integration between HRM and HPM creates superior competitive advantage compared to isolated implementation of either function (β = 0.356, p < 0.001). The study identifies halal organizational culture, employee halal competency, and halal supply chain integration as critical mediating mechanisms. Results indicate that SMEs demonstrating strong HRM-HPM collaboration achieve 42% higher halal brand equity and 38% superior market performance compared to those with weak functional integration. These findings contribute to the emerging literature on halal management by demonstrating that competitive advantage in halal markets requires not merely halal certification, but strategic alignment between human capital development and halal operational excellence. The research provides actionable insights for halal SME practitioners, Islamic business scholars, and policymakers seeking to enhance Indonesia's halal industry competitiveness in the global market valued at USD 2.3 trillion.